Membangun Personal Branding melalui Iklan - Wardi, Yunia (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2014)
This objective of the study was to analyze the influence the Ballyhoo, Banner, the Flowers Board, and the Newspaper Advertisement toward the Personal Branding of the Padang Mayor/ Vice Mayor Candidates in the period of 2014-2019 from UNP students perspective. The samples were 180 UNP students. The samples were taken by proportional cluster random sampling. The data were analysed by statistical test of multiple linear regression. The results of the research showed that: the Ballyhoo gave positive and significant influence toward the Personal Branding of the Padang Mayor/Vice Mayor candidates in the period of 2014-2019, whereas the Banner, the Flowers Board, and the Newspaper Advertisement did not influence their Personal Branding.